2012
DOI: 10.1172/jci60256
|View full text |Cite
|
Sign up to set email alerts
|

ChIP sequencing of cyclin D1 reveals a transcriptional role in chromosomal instability in mice

Abstract: Chromosomal instability (CIN) in tumors is characterized by chromosomal abnormalities and an altered gene expression signature; however, the mechanism of CIN is poorly understood. CCND1 (which encodes cyclin D1) is overexpressed in human malignancies and has been shown to play a direct role in transcriptional regulation. Here, we used genome-wide ChIP sequencing and found that the DNA-bound form of cyclin D1 occupied the regulatory region of genes governing chromosomal integrity and mitochondrial biogenesis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 63 publications
6
123
1
Order By: Relevance
“…Previous studies examined transcriptional regulation of the cyclin D1 target genes, LPL, aP2 (49) and miR17/20 (50). ChIP-ChIP demonstrated cyclin D1 and p300 together occupied genes in close proximity to the transcriptional start site (51), and whole genome ChIP-Seq demonstrated enrichment of cyclin D1 at genes that regulate mitosis and chromosomal instability (CIN) in close proximity to the transcriptional start site (52). Together, these studies are consistent with a model in which cyclin D1 functions to regulate transcription in a cdk-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examined transcriptional regulation of the cyclin D1 target genes, LPL, aP2 (49) and miR17/20 (50). ChIP-ChIP demonstrated cyclin D1 and p300 together occupied genes in close proximity to the transcriptional start site (51), and whole genome ChIP-Seq demonstrated enrichment of cyclin D1 at genes that regulate mitosis and chromosomal instability (CIN) in close proximity to the transcriptional start site (52). Together, these studies are consistent with a model in which cyclin D1 functions to regulate transcription in a cdk-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…A direct interaction of cyclin D1 with chromatin was also demonstrated by a ChIP-sequencing study in which tagged cyclin D1 was ectopically expressed in cyclin D1-null mouse embryonic fibroblasts. The authors concluded that cyclin D1 plays a role in chromosomal stability through binding to genes that govern chromosomal integrity 52 .…”
Section: Kinase-independent Transcriptional Rolesmentioning
confidence: 99%
“…Whole-cell lysates (50 mg) were separated by 10% SDS-PAGE gel, and the proteins were transferred to nitrocellulose membrane for Western blot analysis, as previously described, 31 and probed for SIRT1 (catalog number 15404; Santa Cruz Biotechnology), SOD2-AcK68 (provided by Dr. David Gius 29 ), and b-tubulin (catalog number T4026; Sigma-Aldrich).…”
Section: Western Blot Analysismentioning
confidence: 99%